Downplay social justice issues in art education. Issue 2 (1st August 2021) - Pariser, David
From your perspective, what is the place of social justice education (and politics) in the art classroom? Are these topics a distraction from the disciplinary content of visual arts education, as you understand it? From your perspective, what is the disciplinary content of art education?